Masters of meditation and miracles : lives of the great Buddhist masters of India and Tibet - Thondup, Tulku; Talbott, Harold (Boston, Mass. : Shambhala, 1996)
Lively biographies of important masters in the lineage of the Longchen Nyingthig, one of the most popular teachings of the Nyingma school. These 35 realized teachers start with Garab Dorje and include such great masters as Padmasambhava, Jigme Lingpa and Longchenpa up to modern day lamas such as Dzongsar Khyentse Chokyi Lodro, Dilgo Khyentse Rinpoche, Dodrupchen Rinpoche and Chatral Rinpoche. Tulku Thondup includes details of lineages of teachings in the Nyingma school in general, including those of the three major inner tantras - Mahayoga, Anuyoga and Atiyoga (or Dzogchen), as well as the mind transmission of the Buddhas, the symbolic transmission of the knowledge holders, and the oral transmission of the ascetics. Longchen Nyingthig is a cycle of mystical teachings that represent the innermost meditation of Dzogchen as revealed by the great scholar-yogi Jigme Lingpa, who discovered them as terma.
Includes bibliographicalreferences(p. 350-357) and index.
Keywords: Meditation; z